A first-principles study of CO dissociative adsorption on iron nanoparticles supported on doped graphene. (December 2015) - Kim, Sol; Jhi, Seung-Hoon
Abstract: We study Fe13 nanoparticles supported on doped graphene and investigate the dissociative adsorption of CO on the nanoparticles using first-principle calculations. It is found that boron doping enhances the binding energy of Fe13 on the graphene but nitrogen doping reduces it. We show that difference in the work-function and subsequently in the charge transfer causes such behavior in the binding energies. Calculated d -band width and d -band center are well correlated with the Fe binding energy, mostly because of the orbital hybridization effect. We also show that the dissociative adsorption of CO on the Fe-graphene substrate is strongly correlated with the d- band center, which is in turn modulated by the doping concentration. Highlights: Charge transfer from Fe nanoparticle to graphene affected by doping. Hybridization between Fe13 and graphene proportional to binding energy. Strong correlation between Fe13 binding energy and Fe d -electrons. CO dissociative binding energy is gauged by d -band center.